Having inadequate roughages in cold areas in Tanzania? Consider forage oat and barley - Mwendia, Solomon Waweru; Nzogela, Beatus; Mwilawa, Angello; Notenbaert, An (2024)
Proper livestock feeding is key to improving the livestock sector in sub-Saharan Africa. Limited availability of well-performing forage technologies matched with production environment and context is often a constraint to increaseforage quality and quantity for livestock productivity. To contribute towards forage technologies for cold areas, weselected four promising small grain varieties and evaluated them in 2020-21. They included two (Conway, Glamis)oat varieties and two (Rihane, Kounouz) barley varieties. In two village sites in Mufindi District in the southernhighlands of Tanzania, we established trials in a randomised complete block design replicated three times. While thecultivars produced similar dry matter yields (t ha−1), they returned significantly different crude protein (CP %), NeutralDetergent Fiber (NDF %) and in vitro organic matter digestibility. Digestibility was in the order Glamis>Conway>Kounouz>Rihane, while crude protein yield (t ha−1) was in the order Glamis>Kounouz>Rihane>Conway. Basedon dry matter and crude protein yields and digestibility, Glamis oat would be the most preferable in the study area andother similar ecologies